2022
DOI: 10.7759/cureus.24246
|View full text |Cite
|
Sign up to set email alerts
|

Is Edema Zone Volume Associated With Ki-67 Index in Glioblastoma Patients?

Abstract: IntroductionDespite all the progress with genetic mapping and multimodal treatment, the prognosis of Glioblastoma multiforme (GBM) remains poor, with median overall survival (OS) of only 12 to 15 months. Several studies showed correlations between glioblastoma clinic and prognosis factors; however, it doesn`t occur with tumor radiological features. The purpose of this study is to determine possible correlations between the volumetric analysis of glioblastoma compartments and the proliferation index represented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…[24][25][26][27] In a study conducted by Caramanti et al, Ki-67 index was identified as an indicator of tumor aggressiveness, which correlated with the volume of peritumoral edema. [28] In this study, we confirmed that a high Ki-67 index (>27.4%) is a risk factor for recurrence in patients with high-grade gliomas who underwent rvSIB-IMRT. Further research is needed to determine whether an increase in the margin or dose of RT can improve therapeutic outcomes in these patients who has risk factors treated with rvSIB-IMRT.…”
Section: Discussionsupporting
confidence: 79%
“…[24][25][26][27] In a study conducted by Caramanti et al, Ki-67 index was identified as an indicator of tumor aggressiveness, which correlated with the volume of peritumoral edema. [28] In this study, we confirmed that a high Ki-67 index (>27.4%) is a risk factor for recurrence in patients with high-grade gliomas who underwent rvSIB-IMRT. Further research is needed to determine whether an increase in the margin or dose of RT can improve therapeutic outcomes in these patients who has risk factors treated with rvSIB-IMRT.…”
Section: Discussionsupporting
confidence: 79%
“…MRI studies of 70 patients with GB acquired up to one week before surgery. [123] Elevated prognostic capacity of imaging-based risk stratification in patients with diffuse glioma, NOS. 220 patients classified as diffuse glioma, NOS.…”
Section: Major Findingmentioning
confidence: 99%
“…Caramanti and collaborators found a correlation between the volume of tumorinduced oedema measured by MRI and the Ki-67 proliferation index. According to this study, the two parameters might be considered in relation to each other and be prognostic of OS [123] (Figure 13G,H) (Table 2). A preoperative T2-weighted MRI-based radiomics model was developed by Li and collaborators as a survival prognostic tool for HGG patients [118] (Figure 13B-D) (Table 2).…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation